2019
DOI: 10.5152/ejbh.2019.4727
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Mini-Latissimus Dorsi Flap (MLDF) Reconstruction on Shoulder Function in Breast Cancer Patients

Abstract: Objective:The aim of this study is to investigate the effect of mini latissimus dorsi flap (MLDF) reconstruction on ipsilateral shoulder functions. Materials and Methods:Those included in the study are the patients aged between 23 and 73, who were operated with the diagnosis of early breast cancer (cT1-3)N0). The first group includes the patients who had sentinel lymph node biopsy (SLNB) with partial mastectomy. The second group consists of the patients who had axillary lymph nodule dissection (ALND) with part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…This study result is in accordance with the study by Duymaz T et al, that stated the mean age of the patient who underwent mastectomy was between 47-48 years old. 9 The study by Ibraheem MH et 13 Based on the characteristics of the total seroma in this study, the mean total seroma of LABC patients who underwent MRM without LD flap was 694.45 milliliter, Bali, and is the Faculty of Medicine, Universitas Udayana Hospital. This study was conducted from November 2018 until January 2020 by the Department of Surgical Oncology Faculty of Medicine, Universitas Udayana, Bali, Indonesia.…”
Section: Discussionmentioning
confidence: 69%
“…This study result is in accordance with the study by Duymaz T et al, that stated the mean age of the patient who underwent mastectomy was between 47-48 years old. 9 The study by Ibraheem MH et 13 Based on the characteristics of the total seroma in this study, the mean total seroma of LABC patients who underwent MRM without LD flap was 694.45 milliliter, Bali, and is the Faculty of Medicine, Universitas Udayana Hospital. This study was conducted from November 2018 until January 2020 by the Department of Surgical Oncology Faculty of Medicine, Universitas Udayana, Bali, Indonesia.…”
Section: Discussionmentioning
confidence: 69%
“…They reported that impaired shoulder function also led to a poorer quality of daily life in patients 6–12 months after surgery. Another study analyzing 174 patients using the Q-DASH scores showed that LDMF has a negative impact on shoulder function [ 12 ]. Although Zhou et al [ 13 ] showed no significant differences in muscle strength, shoulder range of motion, disabilities of the arm, shoulder, and hand scores between the LDMF and conventional BCS groups, the varied results may be due to the small number of patients analyzed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Another cross-sectional study including 174 patients divided into four groups with difference in axillary surgery [ALND vs. sentinel node (SN)] as well as in breast surgery (BCS vs. LD mini-flap reconstruction) found a negative impact on shoulder function for the group treated by the combination of ALND and LD mini-flap ( 43 ). This may speak to the favour of conventional BCS over LD mini-flap OPS in combination with ALND.…”
Section: Key Contents and Findingsmentioning
confidence: 99%